2020
DOI: 10.7326/m20-3214
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Risk for Intubation or Death in SARS-CoV-2 Infection

Abstract: Obesity has been associated with COVID-19 and with pneumonia and acute respiratory distress syndrome but is also associated with comorbidities that place patients at higher risk. This study examines whether obesity is associated with intubation or death—as well as biomarkers of inflammation, cardiac injury, or fibrinolysis—in the context of COVID-19 disease independent of obesity-related comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
178
7
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(222 citation statements)
references
References 68 publications
30
178
7
7
Order By: Relevance
“…[7] Furthermore, our results provide important insights on the higher risk of COVID-19 related death for low BMIs (≤19kg/m 2 ); while other studies also found this trend in their effect estimates, these were not significant, likely due to their smaller sample sizes. [7,39,40] We also found that mortality risk related to an increased BMI was higher among individuals aged 69 years or younger compared to older adults. Four previous studies are much in line with our findings, while the opposite was reported in a meta-analysis.…”
Section: Possible Explanationsmentioning
confidence: 51%
See 2 more Smart Citations
“…[7] Furthermore, our results provide important insights on the higher risk of COVID-19 related death for low BMIs (≤19kg/m 2 ); while other studies also found this trend in their effect estimates, these were not significant, likely due to their smaller sample sizes. [7,39,40] We also found that mortality risk related to an increased BMI was higher among individuals aged 69 years or younger compared to older adults. Four previous studies are much in line with our findings, while the opposite was reported in a meta-analysis.…”
Section: Possible Explanationsmentioning
confidence: 51%
“…Four previous studies are much in line with our findings, while the opposite was reported in a meta-analysis. [7,33,36,39,40] Finally, we observed the risk of death after a hospitalisation with COVID-19 associated with BMI was higher among females, compared to males. The results of a study conducted among UK Biobank participants were congruent with our findings, while one performed in a New York hospital found a higher risk among males and others found opposite or null differences by sex.…”
Section: Possible Explanationsmentioning
confidence: 83%
See 1 more Smart Citation
“…Interestingly, similar findings were observed in a retrospective series of COVID‐19 patients in New York City, with a positive association between obesity (BMI 35 kg/m 2 ) and ICU admissions in patients younger than 60 years (OR: 3.6 [95% CI: 2.5‐5.3], P < .0001), but not in those who were older than 60 years (OR: 1.5 [95% CI: 0.9‐2.3], P = .10) 23 . While this article was being prepared, Anderson et al also showed that a gradual association between obesity and IMV or death is observed in adults younger than 65 years who were hospitalized for COVID‐19, but not in patients who were older than 65 years 24 . Altogether, this reinforces the need for specific clinical management and dedicated trials in elderly people affected by COVID‐19.…”
Section: Discussionmentioning
confidence: 89%
“…It is possible that individuals with obesity (and with chronic inflammation) mount a delayed inflammatory response after Covid-19-a phenomenon seen with influenza [48]. Previous studies have shown that individuals with obesity may have impaired macrophage activation and B-and T-cell responses after viral infection [14,48] and their ability to control viral replication is impaired. Secondly, BMI may not be an adequate marker of visceral body fat; it serves as a mere surrogate for central or ectopic adiposity [13,30,37].…”
Section: Discussionmentioning
confidence: 99%